Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1207/s15327957pspr0501_3
|View full text |Cite
|
Sign up to set email alerts
|

Social-Cognitive Theory of Personality Assessment

Abstract: This articlepresents a social-cognitive theory ofpersonality assessment. We articulate the implications ofsocial-cognitive theories ofpersonalityfor the question ofwhat constitutes an assessment ofpersonality structure and behavioral dispositions. The theory consists of 5 social-cognitive principles of assessment. Personality assessments should (a) distinguish the task ofassessing internal personality structures and dynamicsfrom that ofassessing overt behavioral tendencies, (b) attend to personality systems th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
117
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(129 citation statements)
references
References 81 publications
2
117
1
1
Order By: Relevance
“…a). But these externalisations may not reflect psychological phenomena, their qualities, or their structures unequivocally or accurately (Cervone, Shadel, & Jencius, 2001;Lewin, 1935;Toomela, 2011). The complex interrelations between behavioural and psychological phenomena can be untangled only if these different kinds of phenomena are explored each in its own right and if a priori assumptions about specific interrelations are avoided.…”
Section: The New Research Paradigm: Meta-theoretical Foundationsmentioning
confidence: 99%
“…a). But these externalisations may not reflect psychological phenomena, their qualities, or their structures unequivocally or accurately (Cervone, Shadel, & Jencius, 2001;Lewin, 1935;Toomela, 2011). The complex interrelations between behavioural and psychological phenomena can be untangled only if these different kinds of phenomena are explored each in its own right and if a priori assumptions about specific interrelations are avoided.…”
Section: The New Research Paradigm: Meta-theoretical Foundationsmentioning
confidence: 99%
“…Participants signed online for a two-part study and in exchange for their time they received two partial credits toward their course requirements. Previous research on KAPA (i.e., Cervone Shadel & Jencius, 2001) demonstrated that participants' demographic characteristics are unrelated to the variable of study here; thus, demographics were not collected from our sample. All participants declared to have at least six months of work experience.…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…Indeed, it is quite possible that there is meaningful variation even within domains (e.g., different goal orientations when interacting with John than with Jane). In terms of understanding depression vulnerability, a social cognitive personality assessment approach would argue for a more bottomup and person-in-context assessment strategy than the Goal Orientation Inventory currently permits (Cervone, Shadel, & Jencius, 2001). A more context-sensitive assessment strategy might also be of more practical use to the clinician, who could then examine how domain specific VS goal orientations might account for problematic depressive reactions with certain types of life events (e.g., social, achievement, etc.…”
Section: Discussionmentioning
confidence: 99%